Antibiotic Management in Bacterial Pneumonia: A Narrative Literature Review - Herdika, Yusri; Rohani Lasmaria (HM Publisher, 2024)
Pneumonia is an acute inflammation of the lung parenchyma caused by various types of microorganisms, such as bacteria, viruses, fungi, and parasites. The use of antibiotics is often faced with many types and inappropriate doses, and using antibiotics for too long can increase the risk of bacteria multidrug resistance (MDR). Therefore, the choice and dosage of antibiotics must be appropriate to reduce the rate of bacterial resistance. The increasing incidence of bacterial resistance is an indicator of failure in treating pneumonia because, apart from clinical improvement, optimal eradication of bacteria should also be the goal in every antibiotic administration. The aim of this literature review is to explain the basis for administering and selecting empiric antibiotics for pneumonia infections as well as appropriate antibiotic management and adequate especially in bacterial pneumonia, to provide a better prognosis.